2007
DOI: 10.1007/s10562-007-9280-9
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Selective Oxidation to Methyl Formate over ReOx/CeO2 Catalysts

Abstract: Methanol selective oxidation to methyl formate was investigated over ReO x /CeO 2 catalysts in terms of Re loading and reaction mechanism. It was found that Re loading with monolayer dispersion on ceria exhibited promising reaction rate of methanol of 16 mmol g cat.-1 h -1 and methyl formate selectivity of about 90% at 513 K. The surface reaction of methanol, formaldehyde, and methyl formate over the ReO x /CeO 2 catalyst was investigated by in situ Fourier transform infrared spectroscopy and it was revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…The sample spinning rate used for all the measurements was 15.0 ± 0.01 kHz. Al(OH) 6 was used as a reference at 0 ppm that is essentially the same as the common standard of 1.5 M Al(NO 3 ) 3 in D 2 O. The pulses angle for acquiring 27 Al spectra was approximately 90°, corresponding to a 1.5 μs pulse width.…”
Section: Scanning Transmission Electron Microscopy (Stem) and Transmimentioning
confidence: 99%
“…The sample spinning rate used for all the measurements was 15.0 ± 0.01 kHz. Al(OH) 6 was used as a reference at 0 ppm that is essentially the same as the common standard of 1.5 M Al(NO 3 ) 3 in D 2 O. The pulses angle for acquiring 27 Al spectra was approximately 90°, corresponding to a 1.5 μs pulse width.…”
Section: Scanning Transmission Electron Microscopy (Stem) and Transmimentioning
confidence: 99%
“…On the other hand, adsorbed methoxy species is formed by the interaction between methanol and the ionic Re species. [22] Therefore, the alkoxide of 1,2-PrD is adsorbed on the Re species. In addition, it has been reported that the interaction of glycerol [15] and tetrahydrofurfuryl alcohol [21] with ReO x and MoO x species is rather strong.…”
Section: Effect Of Reo X Over Rh Metal Particles On the Reaction Mechmentioning
confidence: 99%
“…4 Recently, it received increasing interest due to the fact that Re-based catalysts show high reactivity in many important catalytic reactions such as selective reduction of NO x with NH 3 , selective oxidation of methanol, thiophene hydrodesulfurization, and ammonia synthesis, where the reaction rate is sensitive to the catalyst surface structure. [5][6][7][8][9][10] Particularly, the recent discovery of O-covered faceted Re͑1231͒ for the growth of Co nanoclusters demonstrates that adsorbate-covered faceted metal surfaces are also promising templates for synthesis of active model catalysts with high selectivity. 11,12 Besides their catalytic properties, such nanostructured surfaces might provide a basis for bridging the gap between nanoparticles and single-crystal surfaces.…”
mentioning
confidence: 99%